2020
DOI: 10.9789/2175-5361.rpcfo.v12.7185
|View full text |Cite
|
Sign up to set email alerts
|

The trend of leprosy epidemiological indicators in the elderly population from the ceará state (2002 to 2014)

Abstract: Objetivo: Descrever os indicadores epidemiológicos da hanseníase em idosos no Ceará de 2002 a 2014. Métodos: Estudo ecológico de série temporal exploratória realizado com dados secundários do Sistema de Informação de Agravos de Notificação do Ceará. Resultados: Registrou-se 8.641 casos, destes, 88,29% casos novos e 3,56% recidivas de hanseníase. A detecção de casos novos permaneceu hiperendêmica (63,3/100.000 habitantes). Durante a série analisada, a prevalência de hanseníase manteve-se com valor considerado a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The main findings from the studies indicated that the relapse occurrence time after the initial PCT treatment is equal to or greater than 5 years after clinical cure, with higher prevalence of patients treated for MB 26,27,28,29 . Complementary findings from the cohort studies revealed that relapse cases were more prevalent among cases with positive bacilloscopy when compared to those with negative bacilloscopy in the initial treatment 13,14,15,30,31,32,33,34,35,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] .…”
Section: Characteristics Of the Population And Clinical Aspects Accor...mentioning
confidence: 99%
“…The main findings from the studies indicated that the relapse occurrence time after the initial PCT treatment is equal to or greater than 5 years after clinical cure, with higher prevalence of patients treated for MB 26,27,28,29 . Complementary findings from the cohort studies revealed that relapse cases were more prevalent among cases with positive bacilloscopy when compared to those with negative bacilloscopy in the initial treatment 13,14,15,30,31,32,33,34,35,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] .…”
Section: Characteristics Of the Population And Clinical Aspects Accor...mentioning
confidence: 99%